Photograph of Church Entrance with Reverend Ralph Cox, 1940s
Black and white photograph taken outside St. Paul's Episcopal Church. Inscription on back of photo: "The Rev. Ralph. H. Cox at entrance." Crossed out: "Mrs. Jennie Vierling facing"